Women's Experiences of Change Processes During Intensive Counselling - Cummings, Anne L.; Hallberg, Ernest T. (Canadian Journal of Counselling and Psychotherapy, 2007)
Post-session written responses of six female clients in intensive, short-term counselling (M= 21 sessions) were examined using qualitative analyses to map their change processes. At the end of each session, clients described the most important event in the session, the reason for its importance, their thoughts and feelings during the event, their thoughts in between sessions, and any change that they were experiencing. Two patterns, Consistent Change and Interrupted Change, emerged from the data analysis. The implications of these patterns for understanding change processes in counselling are discussed.